"Death Itself Shall Be Deathless": Transrationalism and Eternal Death in Don DeLillo's Zero K. Issue 3 (27th May 2019) - Ashman, Nathan
ABSTRACT: The status of human mortality in the face of rapid and overwhelming scientific and technological change is by no means a new topic in DeLillo's fiction. For many critics, death fulfills a crucial function in the author's work, its very possibility operating to maintain the boundaries of time and space that are otherwise under threat of disappearance in post war culture. Don DeLillo's eighteenth novel, Zero K (2016), offers an augmented examination of this conjunction between death and technology, depicting an industrial and scientific landscape where fantasies of eternal life can be legitimately realized via radical advances in cryonic technologies. Yet rather than circumventing death and prolonging life as intended, this article argues that DeLillo instead presents cryonic freezing as a form of eternal death. Subsumed within the technological matrix, death's ineluctability is disturbed and remodulated, meaning that temporal and spatial boundaries become violently unhinged and entirely immeasurable. This boundlessness becomes vividly mirrored in the architectural and temporal logic of the "Convergence" facility itself, a "transrational" space that unravels concepts such as time, space, language, and subjectivity.